Early ICD lead failure in defibrillator systems with multiple leads via cephalic access. (16th May 2020) - Barbhaiya, Chirag R.; Niazi, Osama; Bostrom, Jack; Patil, Sachi; Jankelson, Lior; Bernstein, Scott; Park, David; Holmes, Douglas; Aizer, Anthony; Chinitz, Larry A.
Abstract: Introduction: Implantable cardioverter defibrillators (ICDs) are proven to prevent sudden death in patients at elevated risk for sustained ventricular tachycardia or fibrillation. Complications related to ICD failure can stem from lead dysfunction, manufacturing defects, patient characteristics, or implantation technique. We conducted a review of all ICD leads implanted at our center from 2011 to 2017 to determine risk factors for premature lead failure. Methods: We conducted a retrospective review of patients of all ICD leads implanted from December 2011 to June 2017 at our institution. A total of 660 patients (Biotronik Linox S/SD, n = 281; Sprint Quatro, n = 207; Durata, n = 121; Endotak, n = 51) underwent ICD implantations. Patient and lead characteristics, procedural outcomes and complications were recorded. Lead failure was defined per Heart Rhythm Society lead‐management consensus as a lack of procedural or clinical success, thus requiring an extraction of the lead. Patient and lead outcomes were recorded and variables associated with lead failure were assessed by the Kaplan‐Meier method. Results: Overall failure rate was similar for all leads: Linox S/SD—0.29%/year; Sprint Quattro—0.21%/year, Durata—0.39%/year and Endotak Reliance—0.0% ( P  = .769). No difference was found in overall survival when comparing all ICD manufacturers during the study period. Subgroup analysis revealed the risk of premature lead failure was particularly pronounced in multi‐lead ICD systems implanted via cephalic access ( P  < .001). The estimated failure rate of Linox leads implanted via cephalic access in multi‐lead systems was 19%/year. The estimated failure rate of non‐Linox leads implanted via cephalic access in multi‐lead systems was 11%/year. Neither age, nor gender were risk factors for lead failure in the Linox, or non‐Linox cohorts. Conclusion: All analyzed ICD leads were found to have a similar overall risk of premature failure. ICD lead implantation via cephalic access in multilead ICD systems may be a previously unidentified risk factor for premature ICD lead failure, although these findings require further validation.